Issues on customary marriage and its registration in the Cordillera, Northern Philippines - Prill-Brett, June (Public Policy, 2016)
One of the key debates surrounding the issue of marriage pertains to whether the act is to be considered part of the public or the private domain. As an institution widely regraded to be a foundation of society, marriage is primarily seen as a contract binding two equal and autonomous individuals who would then share the responsibility of reproducing and raising the next generation of citizens that would sustain society. The act of marriage, therefore, is usually publicized, registered and, to a certain extent, regulated by state authorities. Customary law on marriage in Cordillera, Northern Philippines typifies, in varying degrees and forms, the fundamental requisites for marriage recognition that are also found under national laws. Some divergences, however, are found specifically in the matter of solemnizing, witnessing, and registering the act of marriage. This paper thus aims to present a comparison of customary law vis-a-vis national laws on marriage and its registration, and how their similarities and dissimilarities can be rendered to inform policy recommendations. The comparison is conducted through an extensive review of related literature, ethnographies, government policies and official reports from the Local Registrar's Offices in the Cordillera. The paper also reports that a good number of indigeneous peoples still perform customary marriage ceremonies together with civil law and/ or canonical weddings. The former is done in order to express their cultural values, and the latter to comply with stringent legal requirements for securing related official documents to be used in claiming state-sponsored benefits and privileges. In conclusion, issues surrounding the registration of customary marriages are discussed along with policy recommendations on how existing laws on marriage and its registration may be improved for the benefit of indigenous peoples.